Predators can influence the host‐parasite dynamics of their prey via nonconsumptive effects. Issue 13 (12th June 2020) - Zukowski, Nicolette; Kirk, Devin; Wadhawan, Kiran; Shea, Dylan; Start, Denon; Krkošek, Martin
Abstract: Ecological communities are partly structured by indirect interactions, where one species can indirectly affect another by altering its interactions with a third species. In the absence of direct predation, nonconsumptive effects of predators on prey have important implications for subsequent community interactions. To better understand these interactions, we used a Daphnia ‐parasite‐predator cue system to evaluate if predation risk affects Daphnia responses to a parasite. We investigated the effects of predator cues on two aspects of host–parasite interactions (susceptibility to infection and infection intensity), and whether or not these effects differed between sexes. Our results show that changes in response to predator cues caused an increase in the prevalence and intensity of parasite infections in female predator‐exposed Daphnia . Importantly, the magnitude of infection risk depended on how long Daphnia were exposed to the cues. Additionally, heavily infected Daphnia that were constantly exposed to cues produced relatively more offspring. While males were 5× less likely to become infected compared to females, we were unable to detect effects of predator cues on male Daphnia –parasite interactions. In sum, predators, prey, and their parasites can form complex subnetworks in food webs, necessitating a nuanced understanding of how nonconsumptive effects may mediate these interactions. Abstract : We used a Daphnia ‐parasite‐predator cue system to evaluate if predation risk affects Daphnia responses to a parasite. We investigated the nonconsumptive effects of predator cues on two aspects of host–parasite interactions (susceptibility to infection and infection intensity), and whether or not these effects differed between sexes. Our results indicate that changes in response to predator cues caused an increase in the prevalence and intensity of parasite infections in female predator‐exposed Daphnia ; however, the magnitude of infection risk depended on how long Daphnia were exposed to the cues.